2020
DOI: 10.2174/1389201021666200107115849
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using Artocarpus hirsutus Seed Extract and its Antibacterial Activity

Abstract: Aim: To evaluate the antibacterial activity of Artocarpus hirsutus mediated seed extract for nanoparticle synthesis. Background: Gastro-intestinal bacteria are known for causing deadly infections in humans. They also possess multi-drug resistance and interfere with clinical treatments. Applied nanotechnology has been known to combat such infectious agents with little interference from their special attributes. Here we synthesize silver nanoparticles from Artocarpus hirsutus seed extract against two gastro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The plant sources or plant source derivatives associated with nanoparticles are considered as a novel therapy due to their natural care, healthier effectiveness without any side impact, simple way of synthesis and, most importantly less cost. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant sources or plant source derivatives associated with nanoparticles are considered as a novel therapy due to their natural care, healthier effectiveness without any side impact, simple way of synthesis and, most importantly less cost. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…The plant sources or plant source derivatives associated with nanoparticles are considered as a novel therapy due to their natural care, healthier effectiveness without any side impact, simple way of synthesis and, most importantly less cost. 3,4 Nanotechnology is the most advanced technology and it has numerous applications, including several industrial fields and also in human health drug developments because of its nanosize, it has several positive approaches. Nanotechnology has been designated as the next revolution to hit many industries and it can be achieved accredited by scientists to the next step with the existing performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an extract of the stem bark of A. elasticus has been used as a reducing and stabilizing agent for the synthesis of silver nanoparticles (Abdullah et al 2015). The same type of antibacterial silver nanoparticles have been obtained with seed extract of A. hirsutus (Shobana et al 2020).…”
Section: Artocarpus Elasticus and Its Medicinal Usesmentioning
confidence: 97%
“…14 Plant-mediated synthesis provides major benefits, including its ease of monitoring, low time consumption, low cost, and effective replacement of chemicals in the reduction process, and is the safest choice to produce silver nanoparticles. 5,15,16 Recent studies have reported that parts of the plant used for biosynthesized silver nanoparticles are roots, 17 leaves, [18][19][20] seeds 21,22 and bark. 23 Plant extracts contain many bioactive compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that parts of the plant used for biosynthesized silver nanoparticles are roots, 17 leaves, 18–20 seeds 21,22 and bark. 23 Plant extracts contain many bioactive compounds ( e.g.…”
Section: Introductionmentioning
confidence: 99%